Self-assembled cylindrical and vesicular molecular templates for polyaniline nanofibers and nanotapes - Anilkumar, P.; Jayakannan, M. (Journal of Physical Chemistry B, 2009)
We report a soft template approach based on a custom-designed novel surfactant-cum-dopant for size and shape tuning of polyaniline nanomaterials such as nanofibers and nanotapes via emulsion and dispersion polymerization routes. A new amphiphilic 4-(3-dodecyl-8-enylphenyloxy) butane sulfonic acid was synthesized by ring-opening of butanesultone with renewable resource cardanol. The new amphiphilic dopant forms spherical micelles in water and its critical micelle concentration was determined by dye encapsulation and surface tension methods. In the emulsion route, the amphiphilic dopant complexed with aniline to produce cylindrical micellar aggregates that template exclusively for polyaniline nanofibers. The dispersion of aniline + dopant in water/toluene solvent mixture produces vesicles that selectively template for polyaniline nanotapes. The mechanism of the polyaniline nanomaterials formation was investigated by dynamic light scattering (DLS) and high-resolution transmission electron microscopy (HR-TEM). DLS of the polymerization templates in water proved the presence of micrometer range aggregates, and TEM images confirmed the shape of the cylindrical and vesicular templates. The polyaniline nanomaterials were found soluble in water and polar organic solvents for structural characterization and composition analysis by H-1 NMR spectroscopy. Absorbance spectra of the nanomaterials showed free carrier tail above 900 nm in the near IR region for the delocalization of electrons in the polaron band Corresponding to expanded conformation of polyaniline chains, Wide angle X-ray diffraction showed two new peaks at low angle region with d-spacing of 26.5 and 13.6 angstrom Corresponding to lamellar ordering of polyaniline chains followed by interdigitations of the amphiphilic dopant in the nanomaterials.